2018
DOI: 10.1097/md.0000000000013411
|View full text |Cite
|
Sign up to set email alerts
|

NRAGE is a potential diagnostic biomarker of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers and a leading cause of cancer-related deaths worldwide. Early diagnosis of HCC remains a great challenge in clinic. Novel and effective biomarkers are in urgent need in early diagnosis of HCC.Serum levels of neurotrophin-receptor-interacting melanoma antigen-encoding gene homolog (NRAGE) were measured for 107 patients with HCC, 98 patients with benign liver diseases, and 89 healthy controls using quantitative real-time polymerase chain reaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Recently, bioinformatics analyses have been used for identifying novel diagnosis markers and therapeutic targets for many cancers 2123. Zou et al24 identified NRAGE as a novel biomarker for HCC by integrated bioinformatics analysis. Furthermore, in early HCC, the G2/M checkpoint participated in the progression 25.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, bioinformatics analyses have been used for identifying novel diagnosis markers and therapeutic targets for many cancers 2123. Zou et al24 identified NRAGE as a novel biomarker for HCC by integrated bioinformatics analysis. Furthermore, in early HCC, the G2/M checkpoint participated in the progression 25.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, NRAGE was reported as a cancer suppressor gene, which promotes cell apoptosis via binding to p75 neurotrophin receptor (P75NTR) (16,17), Che-1 (18), XIAP-TAK1-TAB1 (19), and UNC5H1 (20) and inhibits proliferation (21) and angiogenesis (22). Contradictorily, functions such as pro-apoptotic gene and growth promotion were slowly discovered (12)(13)(14)(23)(24)(25)(26). Kodera et al (25) found that increased NRAGE expression affects the malignant phenotype of hepatocellular carcinoma (HCC) via its interaction with apoptosis antagonizing transcription factor (AATF).…”
Section: Introductionmentioning
confidence: 99%
“…Kodera et al (25) found that increased NRAGE expression affects the malignant phenotype of hepatocellular carcinoma (HCC) via its interaction with apoptosis antagonizing transcription factor (AATF). Zou et al (24) proved that NRAGE may be a potential biomarker for HCC early diagnosis due to its ability of distinguishing HCC from benign liver disease. Yang et al (26) reported that an aberrant NRAGE expression in both mRNA and protein levels in ESCC tissues was detected and could induce DNA-damaging chemoresistance by regulating homologous recombination repair.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, NRAGE was reported as a cancer suppressor gene, which promotes cell apoptosis via binding to P75NTR [13], Che-1 [14], XIAP-TAK1-TAB1 [15], and UNC5H1 [16] and inhibits proliferation [17] and angiogenesis [18]. Contradictorily, functions such as pro-apoptotic gene and growth promotion were slowly discovered [9,11,[19][20][21][22]. Kodera et al [21] found that increased NRAGE expression affects the malignant phenotype of HCC via its interaction with AATF.…”
Section: Introductionmentioning
confidence: 99%
“…Kodera et al [21] found that increased NRAGE expression affects the malignant phenotype of HCC via its interaction with AATF. Zou et al [20] proved that NRAGE may be a potential biomarker for HCC early diagnosis due to its ability of distinguishing HCC from benign liver disease. Yang et al [22] reported that an aberrant NRAGE expression in both mRNA and protein levels in ESCC tissues was detected and could induce DNA-damaging chemoresistance by regulating homologous recombination repair.…”
Section: Introductionmentioning
confidence: 99%